Writing Between "the Human" and "the Animal" in Margaret Atwood's MaddAddam Trilogy ... - Skibo-Birney, Bryn (Université de Genève, 2020)
Through narratological analyses of Margaret Atwood's MaddAddam trilogy, this project challenges the ingrained epistemologies and ontologies of humanism and anthropocentrism and offers a zoecentric alternative: the “individual” is always-already hybrid. Beginning with a post-structural and post-humanist theoretical framework, Part I explores how Atwood constructs hybrid Bildungsromans in Crake and Flood by aligning narratively significant moments of inter-species interaction with substantial shifts of the binary narrative structure. Both novels end, however, on unresolved binary options. Part II introduces Anishinaabe epistemologies and ontologies of interconnectivity, using the philosophy of mino-bimaadiziwin alongside aspects of Anishinaabemowin and narrative forms, in order to conduct an Indigenous-centric reading of MaddAddam. I argue that the trilogy both depicts and performs a zoecentric epistemological/ontological shift in the development of the characters, the narrative structure, and the trilogy as a ...